Presupposition And [e]motion : The Upgraded Function and the Semantics of the Participle in the New Testament - Albuquerque, Roque N. (Peter Lang Publishing, Incorporated, 2020)
Cover -- Contents -- List of Figures -- Abbreviations -- Preface -- Chapter One: Introduction -- Statement of the Problem -- Definition of Terms -- The History of the Upgraded Participle -- Neglect of the Upgraded Function of the Participle -- Absence of Definitive Guidelines -- The Purpose of the Study -- The Method of the Study -- Ramifications of the Study -- Summary of the Study -- Chapter Two: Participle as Semantic Presupposition -- A Theory of Grammar -- Systemic Functional Linguistics -- Verbal Aspect, Modal Semantic and SFL: Caveat and Implementation -- Semantics and Pragmatics: Closed and Open Systems in Linguistics -- The Study of Register -- Presupposition -- Semantic and Pragmatic Presupposition -- The Study of Presupposition -- Presupposition and Given-New/Theme-Rheme -- Presupposition as Shared Information -- Chapter Three: Greek Participles: Modulation Versus Modality and Mood -- Function and Form: Semiotic Component and Functional Component -- Assertive and Non-assertive Attitudes -- Modulation: Participle a Quasi- Modality -- Chapter Four: Functions of the Participle -- Background Function -- Background: Theory of Verbal Aspect and the Aorist Adverbial Participles -- Aspect of the Participle -- A New Approach in the Analysis of the Participle -- Prioritizing Function -- Markedness and Modulational Prioritizing Function -- Aorist Participle: Background/Prioritization and Clause Chain -- Greek Participles and [E]‌motion -- Emotion and the Readers ≠ Participle and Emotion -- Upgraded Effect and [E]‌motion -- Chapter Five: Semantics of the Upgraded Participle -- The Upgraded Participle in the New Testament -- Structure of the Upgraded Participle: Grammar -- Word Order with the Upgraded Participle -- Grammatical (Morphological, Structural) -- Contextual -- Structure of the Upgraded: Pragmatics.